The Judicialization of Politics, Judicial Activism: Challenges of Democracy in Brazil - Ningeliski, Adriane de Oliveira (2016)
The changes of the economic order, of values and thoughts of society, have increasingly led the Judiciary to intervene actively in issues that, primarily, would be out of its competence, due to an evident inertia of the other State powers, which are politically elected and as representatives of the majority, end up not fulfilling their role of protection and guarantee of the collectivity. This interference has led to tensions between the powers, giving rise to a heated discussion about a possible offense to the democratic principle. Thus, from the dialectical method, the present research seeks to highlight these concerns.